Corn Cost-Return Budget in North Central Kansas - Dumler, Troy J.; Duncan, Stewart R. (My University, 2005)
This publication provides estimated cost and returns for forward farm planning for corn production in north central Kansas.
MF2161_2005_10
Keywords: MF2161; Crops; Economics; MF